Amyloid beta peptides inside a reconstituted cell-like liposomal system: aggregation, FRET, fluorescence oscillations and solvation dynamics. Issue 44 (26th October 2016) - Nandi, Somen; Mondal, Prasenjit; Chowdhury, Rajdeep; Saha, Abhijit; Ghosh, Surajit; Bhattacharyya, Kankan
Abstract : The aggregation dynamics of Aβ peptides were studied inside a reconstituted cell-mimic liposomal system using FRET and FCS at various depths starting from the membrane to the core of the liposome. Abstract : Aggregations of amyloid-beta (Aβ) peptides were studied inside a reconstituted cell like liposomal system using time-resolved confocal microscopy. Fluorescence correlation spectroscopy (FCS) and confocal images indicate that Aβ forms a very large aggregate in bulk and more efficiently, in the bilayer region of the liposome, respectively. The aggregates formed inside the liposome gradually migrate out to bulk water. FRET, from HiLyte Fluor 488 (covalently attached to an Aβ peptide) to TRITC (tetramethylrhodamine isothiocyanate) covalently attached to a DHPE lipid present in the bilayer, reveals intermittent oscillations in the time scale of ∼0.5 s. This is attributed to the structural fluctuations of the membrane of the liposome. The solvation dynamics of Aβ in monomer and in oligomeric state is studied by monitoring the emission of HiLyte Fluor 488. The solvation dynamics of the Aβ monomer is similar to that of oligomeric aggregates in the liposome.